Urgensi Peraturan Daerah Pengelolaan Daerah Aliran Sungai Bengawan Solo dalam Rangka Penguatan Fungsi Lingkungan Hidup dan Good Governance - I Gusti Ayu Ketut Rachmi Handayani (Fakultas Hukum Universitas Islam Indonesia, 2013)
The damage of Drainage Basin (DAS) comes to be a factor on the unavoidable flooding disaster area. In Indonesia, most of Drainage Basins – particularly in Java including Bengawan Solo Drainage Basin have experienced damage. This research is to analyze the urgency of the local regulation on the management of Bengawan Solo Drainage Basin in order to strengthen the function of ecosystem and good government. The method used in this research is a judicial-empirical or non- doctrinal method. The result of the research concludes that in such condition in which the threat of the crisis of support capability on ecosystem and environment being faced by Indonesia is so real. Hence, legislation of legal norms on the management of Integrated Drainage Basin at Bengawan Solo is highly needed along with the intention to strengthen the democracy and constitutional state and management of Good Governance. On the other hand, in Central Government, there has been Government Regulation No. 37 Year 2012 about the Management of Drainage Basin and it is time to follow up in the form of Local Regulation.